Audit Committee Quality and Financial Reporting Quality: A Study of Selected Indian Companies - Shankaraiah, Kanukuntla; Sajjadian Amiri, Seyed Masoud (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
This study examines audit committee quality and its relationship with financial reporting quality. The population of this study consists of the companies listed in Bombay Stock Exchange (BSE) between years 2002 and 2012. Using Godden sample size formula, 133 companies are selected randomly for the study. It is found that in most of the equity based listed companies at BSE under study have complied with the legal formalities, for instance, appointment of independent directors, number of meetings, size of the audit committee, legal qualifications and financial qualifications of the directors, as they were required for the listing at a stock exchange in India. Further, the analysis and tests state that board size, audit committee meetings and its size have relationship with the financial reporting practices, but the CEO tenure and hold, board independence, net income, proportion of independent directors on board, legal qualifications and financial qualifications of the directors and overlap of audit committee members on compensation committee, have no influence on the financial reporting practices. Thus, it may be inferred that the companies may improve the financial reporting quality, by managing the board size, audit committee meetings and size, as these characteristics have significant relationship with financial reporting quality.